Strong Convergence on the Split Feasibility Problem by Mixing W-Mapping - Fugen Gao; Xiaoxiao Liu; Xiaochun Li (Journal of Mathematics)
In this paper, we concern with the split feasibility problem (SFP) in real Hilbert space whenever the sets involved are nonempty, closed, and convex. By mixing W-mapping with the viscosity, we introduce a new iterative algorithm for solving the split feasibility problem, and we prove that our proposed algorithm is convergent strongly to a solution of the split feasibility problem.